Green Buildings in the Arctic region: a literature review - Ravasio Lucrezia; Riise Raymond; Sveen Svein Erik (E3S Web of Conferences, 2020)
Green Buildings are defined as environmental-friendly buildings aimed at minimizing the impact on the natural environment through a sustainable and efficient use of resources over their life-cycle. This is, perhaps, a recently-introduced building concept that is increasingly gaining attention due to the policies and strategies intended to reduce the carbon footprint of conventional buildings, which nowadays represent a large portion of the global energy consumption and C02 emissions. This study provides a systematic literature review of the existing body of knowledge of research related to Green Buildings in the arctic region. Despite numerous studies and projects developed during the last decades, a study describing the current research for this specific region is still missing. Starting from the definition of Green Building and Arctic Region, an examination is made of research approaches developed to achieve the required green building standards, for which rating tools currently in use for their evaluation are also identified. The result is a critical analysis highlighting benefits and critical issues of Green Buildings located in the Arctic in comparison with conventional buildings, focusing on the environmental, economic and social dimensions. Finally, future research opportunities are presented and discussed.